2016
DOI: 10.5624/isd.2016.46.3.185
|View full text |Cite
|
Sign up to set email alerts
|

IDIOS: An innovative index for evaluating dental imaging-based osteoporosis screening indices

Abstract: PurposeThe goal of this study was to develop a new index as an objective reference for evaluating current and newly developed indices used for osteoporosis screening based on dental images. Its name; IDIOS, stands for Index of Dental-imaging Indices of Osteoporosis Screening.Materials and MethodsA comprehensive PubMed search was conducted to retrieve studies on dental imaging-based indices for osteoporosis screening. The results of the eligible studies, along with other relevant criteria, were used to develop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 114 publications
(108 reference statements)
0
14
0
Order By: Relevance
“…It was found that the cortical bone measurements (thickness or density) could reflect the changes in the skeletal BMD, in contrast to the trabecular bone measurements . This result was confirmed in a 24‐year follow‐up study .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It was found that the cortical bone measurements (thickness or density) could reflect the changes in the skeletal BMD, in contrast to the trabecular bone measurements . This result was confirmed in a 24‐year follow‐up study .…”
Section: Discussionmentioning
confidence: 72%
“…This would make the investigation process better. The used indices are good indices for osteoporosis screening from dental radioimages …”
Section: Discussionmentioning
confidence: 99%
“…However, access to DXA examination is significantly limited in a number of countries . Fortunately, obtaining evidence of osteoporotic alterations is also possible by assessing radiomorphometric indices on panoramic radiographs, which are widely applied in dental clinical practice because of their low cost and wide availability. Among the radiomorphometric indices, the mandibular cortical index (MCI) is useful for screening postmenopausal women at risk of osteoporosis because it is inversely correlated with systemic BMD .…”
Section: Introductionmentioning
confidence: 99%
“…Second, OSTA was the only measurement representing osteoporosis and fracture risk in this study. Future studies should search a link between other markers of osteoporosis and arterial stiffness, such as Mandibular cortical width, a marker of osteoporosis detected by dental panoramic radiographs (40). Third, information such as physical activity and alcohol consumption were not collected.…”
Section: Discussionmentioning
confidence: 99%